Procesele de pauperizare, rezultat al modificărilor de sistem în perioada de tranziţie - Patrzalek, Wanda (Calitatea Vieții, 1992)
Wanda Patrzalek, scientific researcher at the Institute of Sociology belonging to the Wroclaw University approaches in her paper the topic concerning the social consequences of the transition period and the polarization implied.